Infrared stealth coating for aircraft and preparation method thereof
By using composite materials of collagen, ITO powder, polyaniline composites and specific additives, the problem of insufficient bonding and stealth performance of existing infrared stealth coatings is solved, and higher coating integrity, hardness and stealth effects are achieved.
Patent Information
- Application Number
- CN202510286321.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The bonding and stealth performance of existing infrared stealth coatings when used need to be further improved.
The composite materials of collagen, ITO powder, polyaniline composite and specific additives are used to form infrared stealth coatings through specific preparation steps to improve the integrity, hardness and wear resistance of the coating.
It achieves more stable coating performance, expands the infrared absorption range, improves the hardness, wear resistance and adhesion of the coating, and enhances the stealth effect.
Smart Images

Figure CN119775895A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of infrared stealth coatings, in particular to an infrared stealth coating for aircraft and a preparation method thereof. Background Art
[0002] A Chinese patent discloses an infrared stealth coating and a preparation method thereof (Announcement No.: CN118006205A). The infrared stealth coating includes the following raw materials: an organic adhesive, a filler, a pigment, a dispersant, a thickener, a leveling agent, a defoaming agent, a film-forming aid and water; wherein the filler is a composite material of doped metal semiconductor materials and tubular nanomaterials; the preparation method of the coating of the application is: firstly weigh the pigment, dispersant, thickener, leveling agent, defoaming agent, film-forming aid and water by weight percentage and mix them evenly to obtain liquid A; then weigh the organic adhesive by weight percentage and mix them evenly with liquid A to obtain liquid B; finally weigh the filler by weight percentage and mix them evenly with liquid B to obtain the infrared stealth coating; the infrared stealth coating prepared by the application improves the infrared absorption rate of the coating film, enhances its stealth performance, and improves the mechanical properties of the coating film. However, the bonding performance and stealth performance of the infrared stealth coating prepared by the above-mentioned prior art solutions need to be further improved during use; to this end, the present invention proposes an infrared stealth coating for aircraft and a preparation method thereof to solve the above-mentioned problems. Summary of the invention
[0003] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides an infrared stealth coating for aircraft and a preparation method thereof, which solves the problems mentioned in the above background technology.
[0004] (II) Technical solution To achieve the above objectives, the present invention is implemented through the following technical scheme: an infrared stealth coating for aircraft, which includes the following components: 20-35g of collagen, 45-65mL of deionized water, 50-60mL of acetone, 12-25g of ITO powder, 7.5-14g of adhesive, 7-12g of polyaniline composite, and 16-25g of additive.
[0005] A method for preparing an infrared stealth coating for an aircraft, specifically comprising the following preparation steps: Step 1: Dissolve collagen in deionized water, add acetone under stirring, and continue stirring for 50 to 70 minutes; Step 2: Add ITO powder with a tin content of 6.5% to 8.5%, then heat to 50 to 60°C, keep warm for 5 to 6 hours, cool to room temperature, and then filter, wash and dry in sequence; Step 3: first add the auxiliary agent, stir for 5 to 10 minutes, then add the polyaniline compound, stir for 15 to 20 minutes, and finally add the adhesive, stir and disperse at high speed for 50 to 60 minutes to obtain the infrared stealth coating for aircraft; The auxiliary agent includes 50wt% to 80wt% of polyvinyl alcohol as a dispersant and 20wt% to 50wt% of polymethylphenylsiloxane as a leveling agent.
[0006] Preferably, the preparation method of the adhesive is: (1) Pour the polymer, solvent and one-third of the initiator into a four-necked flask and stir until the polymer is completely dissolved; (2) Pour the monomer, solvent and remaining initiator into a dropping funnel, raise the temperature at a rate of 2-5°C / min under stirring, and when the temperature reaches 75-85°C, keep it warm for 10-15 minutes, then add it dropwise to the four-necked flask; (3) Continue to raise the temperature to 100-120°C and react for 8-9 hours to obtain the adhesive.
[0007] Preferably, the added weight of each component in the adhesive is: 10 to 30 parts of polymer, 70 to 90 parts of monomer, 0.1 to 0.35 parts of initiator, and 80 to 100 parts of solvent.
[0008] Preferably, the polymer is selected from any one of polybutadiene and EPDM; the monomer is selected from any one or more of methyl methacrylate, butyl acrylate, hexyl acrylate, methyl acrylate, and acrylic acid; the solvent is selected from any one of xylene, toluene, butyl acetate, tetrahydrofuran, and n-butanol; and the initiator is selected from any one of azobisisobutyronitrile and benzoyl peroxide.
[0009] Preferably, the specific preparation process of the polyaniline composite comprises the following steps: Ⅰ. Pour 80-100 mL of 1 mol / L camphorsulfonic acid into 180-200 mL of deionized water and stir for 10-15 minutes; Ⅱ. Add 0.85-1 mL of aniline with a concentration of 0.2 mol / L dropwise under stirring and stir evenly; III. Cool in an ice-water bath to 2-5°C, and under stirring, dropwise add 45-50 mL of 1.5 mol / L ammonium persulfate, and stir for 4.5-6 hours; IV. After stopping stirring, let it stand for 12 to 14 hours; V. Filter by suction, then wash the precipitate with deionized water and ethanol alternately until the pH value of the filtrate is 7, and then dry it in a vacuum drying oven to constant weight; VI. Pour into 60-90 mL of 1 mol / L HCl solution, grind thoroughly for 50-70 min, and finally dry in a vacuum drying oven to constant weight.
[0010] Preferably, in step III, the ammonium persulfate is added dropwise within 45 to 60 minutes.
[0011] Preferably, in step V and step VI, the drying temperature is 55-65°C.
[0012] (III) Beneficial effects The present invention provides an infrared stealth coating for aircraft and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, since collagen macromolecules are rich in oxygen, nitrogen and other atoms that have a certain affinity for metal oxides, they can be used to modify and stabilize ITO nanoparticles, making the coating more stable during storage and use; and collagen itself has a certain film-forming property, and when added to the coating, it helps to form a continuous and uniform coating, thereby improving the integrity and density of the coating; at the same time, since ITO powder has a relatively high ability to absorb infrared light in different bands, especially in the mid-infrared band, after being compounded with collagen, it can further expand the infrared absorption range, achieve infrared stealth in a wider band, and effectively improve the mechanical properties of the coating, such as hardness, wear resistance, and adhesion.
[0013] (2) In the present invention, since the molecular structure of the polyaniline composite contains polar groups, it can interact with the surface of the ITO powder, thereby having good dispersibility in the ITO powder, making the coating performance more uniform; and the unique molecular structure and electron cloud distribution of the polyaniline composite have a specific absorption peak in the infrared band. After combining with the ITO powder, it can broaden the infrared absorption range, enhance the absorption capacity of infrared light, and reduce the infrared radiation intensity of the target; at the same time, it can form a good conductive network in the coating, effectively attenuate and reflect electromagnetic waves, reduce the reflection of the target to the infrared detection signal, and improve the stealth effect.
[0014] (3) In the present invention, since the ITO powder itself has the characteristic of low infrared emissivity, after being combined with the adhesive, it can not only improve the bonding performance of the coating, but also form a low-emissivity coating on the target surface, effectively reducing the infrared radiation intensity of the target, making the target difficult to be detected under infrared detection equipment; at the same time, it can expand the infrared absorption range, so that the coating has absorption capacity in a wider infrared band, enhance the attenuation effect of infrared light of different wavelengths, and improve the stealth effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a comparison chart of the wear resistance test of the coating provided by the present invention. DETAILED DESCRIPTION
[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] Example 1 A method for preparing an infrared stealth coating for an aircraft, specifically comprising the following preparation steps: Step 1: Dissolve 20 g of collagen in 45 mL of deionized water, add 50 mL of acetone under stirring, and continue stirring for 50 min; Step 2: Add 12 g of ITO powder with a tin content of 6.5%, then heat to 50° C., keep warm for 5 hours, cool to room temperature, and then filter, wash and dry in sequence; Step 3, first add 16g of an additive, wherein the additive includes 50wt% of polyvinyl alcohol and 50wt% of polymethylphenylsiloxane, stir for 5min, then add 7g of polyaniline complex, stir for 15min, and finally add 7.5g of adhesive, stir and disperse at high speed for 50min, to obtain an infrared stealth coating for aircraft; The preparation method of the adhesive is as follows: 10 g of polybutadiene, 40 g of xylene and 0.05 g of azobisisobutyronitrile are poured into a four-necked flask and stirred until the polymer is completely dissolved; 70 g of methyl methacrylate and butyl acrylate in a mass ratio of 1:1, 40 g of xylene and 0.1 g of azobisisobutyronitrile are poured into a dropping funnel, and the temperature is raised at a rate of 2°C / min under stirring. When the temperature rises to 75°C, the temperature is kept for 10 minutes, and then the mixture is added dropwise to the four-necked flask; the temperature is continued to be raised to 100°C and reacted for 8 hours to obtain the adhesive; The specific preparation process of the polyaniline composite is as follows: pour 80 mL of camphorsulfonic acid with a concentration of 1 mol / L into 180 mL of deionized water and stir for 10 minutes; add 0.85 mL of aniline with a concentration of 0.2 mol / L under stirring and stir evenly; cool to 2°C in an ice-water bath, and add 45 mL of ammonium persulfate with a concentration of 1.5 mol / L under stirring, and complete the addition within 45 minutes, and continue to stir and react for 4.5 hours; stop stirring and let stand for 12 hours; filter, then wash the precipitate with deionized water and ethanol alternately until the pH value of the filtrate is 7, and then put it in a vacuum drying oven at 55°C to dry to constant weight; then pour it into 60 mL of HCl solution with a concentration of 1 mol / L, grind it thoroughly for 500 minutes, and finally put it in a vacuum drying oven at 55°C to dry to constant weight.
[0018] Example 2 A method for preparing an infrared stealth coating for an aircraft, specifically comprising the following preparation steps: Step 1: Dissolve 25 g of collagen in 55 mL of deionized water, add 55 mL of acetone under stirring, and continue stirring for 60 min; Step 2: add 18 g of ITO powder with a tin content of 7.5%, then heat to 55° C., keep warm for 5.5 hours, cool to room temperature, and then filter, wash and dry in sequence; Step 3, first add 20g of an additive, wherein the additive includes 70wt% of polyvinyl alcohol and 30wt% of polymethylphenylsiloxane, stir for 8min, then add 10g of a polyaniline complex, stir for 18min, and finally add 10g of a binder, stir and disperse at high speed for 55min, to obtain an infrared stealth coating for aircraft; The preparation method of the adhesive is as follows: 20 g of polybutadiene, 45 g of butyl acetate and 0.09 g of azobisisobutyronitrile are poured into a four-necked flask and stirred until the polymer is completely dissolved; 80 g of hexyl acrylate, 45 g of butyl acetate and 0.18 g of azobisisobutyronitrile are poured into a dropping funnel, and the temperature is raised at a rate of 4°C / min under stirring. When the temperature reaches 80°C, the temperature is kept for 12 minutes, and then the mixture is added dropwise to the four-necked flask; the temperature is continued to be raised to 110°C and reacted for 8.5 hours to obtain the adhesive; The specific preparation process of the polyaniline composite is as follows: pour 90 mL of camphorsulfonic acid with a concentration of 1 mol / L into 190 mL of deionized water and stir for 12 minutes; add 0.9 mL of aniline with a concentration of 0.2 mol / L under stirring and stir evenly; cool to 3°C in an ice-water bath, and add 48 mL of ammonium persulfate with a concentration of 1.5 mol / L under stirring, and complete the addition within 50 minutes, and continue to stir and react for 5 hours; stop stirring and let stand for 13 hours; filter, then wash the precipitate with deionized water and ethanol alternately until the pH value of the filtrate is 7, and then put it in a vacuum drying oven at 60°C to dry to constant weight; then pour it into 75 mL of HCl solution with a concentration of 1 mol / L, grind it thoroughly for 60 minutes, and finally put it in a vacuum drying oven at 60°C to dry to constant weight.
[0019] Example 3 A method for preparing an infrared stealth coating for an aircraft, specifically comprising the following preparation steps: Step 1: Dissolve 35 g of collagen in 65 mL of deionized water, add 60 mL of acetone under stirring, and continue stirring for 70 min; Step 2: Add 25 g of ITO powder with a tin content of 8.5%, then heat to 60° C., keep warm for 6 hours, cool to room temperature, and then filter, wash and dry in sequence; Step 3, first add 25g of an additive, wherein the additive includes 80wt% of polyvinyl alcohol and 20wt% of polymethylphenylsiloxane, stir for 10min, then add 12g of a polyaniline complex, stir for 20min, and finally add 14g of a binder, stir and disperse at high speed for 60min, to obtain an infrared stealth coating for aircraft; The preparation method of the adhesive is as follows: 30 g of EPDM rubber, 50 g of tetrahydrofuran and 0.1 g of benzoyl peroxide are poured into a four-necked flask and stirred until the polymer is completely dissolved; 90 g of monomer, 50 g of tetrahydrofuran and 0.2 g of benzoyl peroxide are poured into a dropping funnel, and the temperature is raised at a rate of 5°C / min under stirring. When the temperature rises to 85°C, the temperature is kept for 15 minutes, and then the temperature is dropped into the four-necked flask; the temperature is continued to be raised to 120°C and reacted for 9 hours to obtain the adhesive; The specific preparation process of the polyaniline composite is as follows: pour 100 mL of camphorsulfonic acid with a concentration of 1 mol / L into 200 mL of deionized water and stir for 15 minutes; add 1 mL of aniline with a concentration of 0.2 mol / L under stirring and stir evenly; cool to 5°C in an ice-water bath, and add 50 mL of ammonium persulfate with a concentration of 1.5 mol / L under stirring, and complete the addition within 60 minutes, and continue to stir and react for 6 hours; after stopping stirring, let it stand for 14 hours; filter, then wash the precipitate with deionized water and ethanol alternately until the pH value of the filtrate is 7, and then put it in a vacuum drying oven at 65°C to dry to constant weight; then pour it into 90 mL of HCl solution with a concentration of 1 mol / L, grind it thoroughly for 70 minutes, and finally put it in a vacuum drying oven at 65°C to dry to constant weight.
[0020] Comparative Example 1 Compared with Example 1, the difference is that collagen is not added; the rest remains unchanged.
[0021] Comparative Example 2 Compared with Example 1, the difference is that no polyaniline composite is added; the rest remains unchanged.
[0022] Comparative Example 3 Compared with Example 1, the difference is that the adhesive is replaced by epoxy resin; the rest remains unchanged.
[0023] The steel plate substrate is pretreated by uniformly sanding with sandpaper, washing with water, chemically degreasing, washing with water, and then drying for use; the coating is evenly applied on the surface of the treated steel plate, and the coating 7 has a thickness of 35 μm.
[0024] Infrared emissivity: measured using an IR-2 dual-band infrared emissivity meter; the results are shown in Table 1.
[0025] Coating hardness: measured using a QHQ paint film pencil scratch hardness tester; the results are shown in Table 1.
[0026] Coating adhesion: The coating adhesion tester was used to measure the coating adhesion. The results are shown in Table 1.
[0027] Table 1 Test results of coating infrared emissivity, hardness and adhesion Coating wear resistance: measured using a QMH coating wear tester; the results are as follows Figure 1 As shown: compared with comparative examples 1-3, especially compared with comparative example 1, the weight loss of the coatings prepared in embodiments 1-3 is significantly smaller, indicating that the coatings have excellent wear resistance.
[0028] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0029] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An infrared stealth coating for aircraft, characterized in that: The infrared stealth coating comprises the following components: 20-35 g of collagen, 45-65 mL of deionized water, 50-60 mL of acetone, 12-25 g of ITO powder, 7.5-14 g of adhesive, 7-12 g of polyaniline composite, and 16-25 g of auxiliary agent.
2. A method for preparing an infrared stealth coating for aircraft according to claim 1, characterized in that: The specific preparation steps include: Step 1: Dissolve collagen in deionized water, add acetone under stirring, and continue stirring for 50 to 70 minutes; Step 2: Add ITO powder with a tin content of 6.5% to 8.5%, then heat to 50 to 60°C, keep warm for 5 to 6 hours, cool to room temperature, and then filter, wash and dry in sequence; Step 3: first add the auxiliary agent, stir for 5 to 10 minutes, then add the polyaniline compound, stir for 15 to 20 minutes, and finally add the adhesive, stir and disperse at high speed for 50 to 60 minutes to obtain the infrared stealth coating for aircraft; The auxiliary agent includes 50wt% to 80wt% of polyvinyl alcohol as a dispersant and 20wt% to 50wt% of polymethylphenylsiloxane as a leveling agent.
3. The method for preparing an infrared stealth coating for aircraft according to claim 2, characterized in that: The preparation method of the adhesive is: (1) Pour the polymer, solvent and one-third of the initiator into a four-necked flask and stir until the polymer is completely dissolved; (2) Pour the monomer, solvent and remaining initiator into a dropping funnel, raise the temperature at a rate of 2-5°C / min under stirring, and when the temperature reaches 75-85°C, keep it warm for 10-15 minutes, then add it dropwise to the four-necked flask; (3) Continue to raise the temperature to 100-120°C and react for 8-9 hours to obtain the adhesive.
4. The method for preparing an infrared stealth coating for aircraft according to claim 3, characterized in that: The added weights of the components in the adhesive are: 10 to 30 parts of polymer, 70 to 90 parts of monomer, 0.1 to 0.35 parts of initiator and 80 to 100 parts of solvent.
5. The method for preparing an infrared stealth coating for aircraft according to claim 3, characterized in that: The polymer is selected from any one of polybutadiene and EPDM; the monomer is selected from any one or more of methyl methacrylate, butyl acrylate, hexyl acrylate, methyl acrylate and acrylic acid; the solvent is selected from any one of xylene, toluene, butyl acetate, tetrahydrofuran and n-butanol; the initiator is selected from any one of azobisisobutyronitrile and benzoyl peroxide.
6. The method for preparing an infrared stealth coating for aircraft according to claim 2, characterized in that: The specific preparation process of the polyaniline composite is as follows: Ⅰ. Pour 80-100 mL of 1 mol / L camphorsulfonic acid into 180-200 mL of deionized water and stir for 10-15 minutes; Ⅱ. Add 0.85-1 mL of aniline with a concentration of 0.2 mol / L dropwise under stirring and stir evenly; III. Cool in an ice-water bath to 2-5°C, and under stirring, dropwise add 45-50 mL of 1.5 mol / L ammonium persulfate, and stir for 4.5-6 hours; IV. After stopping stirring, let it stand for 12 to 14 hours; V. Filter by suction, then wash the precipitate with deionized water and ethanol alternately until the pH value of the filtrate is 7, and then dry it in a vacuum drying oven to constant weight; VI. Pour into 60-90 mL of 1 mol / L HCl solution, grind thoroughly for 50-70 min, and finally dry in a vacuum drying oven to constant weight.
7. The method for preparing an infrared stealth coating for aircraft according to claim 6, characterized in that: In the step III, the ammonium persulfate is added dropwise within 45 to 60 minutes.
8. The method for preparing an infrared stealth coating for aircraft according to claim 6, characterized in that: In step V and step VI, the drying temperature is 55-65°C.
Citation Information
Patent Citations
Infrared camouflage coating and preparation method thereof
CN118006205A
Cited By
Infrared stealth composite coating system compatible with low-lightness visible light camouflage and preparation method thereof
CN120890309A